Variation and Phenotypic Evaluation of Intraspecific Oryza glaberrima Lines Resulting from Crossings between Tog5681, Tog5672 and Tog7291 - Agnoun, Y.; Ahounou, E.; Sié, M.; Ogunbayo, S.A.; Toulou, B.; Futakuchi, K.; Ahanchédé, A. (Canadian Center of Science and Education, 2012)
Rice cultivation in Africa suffers from various biotic and abiotic constraints. The African rice, Oryza glaberrima, is a potential source of useful genes for resistance to a range of these stresses. The development of interspecific varieties based on crosses between the high yielding cultivated Asian rice species (Oryza sativa) and O. glaberrima showed some gaps in the resistance compared to O. glaberrima. In order to valorize its genetic potential, intraspecific lines were developed using three O. glaberrima lines Tog5681, Tog5672 and Tog7291 as parents. Phenotypic evaluation of the progeny (total of 55 F6 lines) and checks (O. glaberrima and O. sativa) using 18 quantitative characters, showed a higher degree of variation in plant height, leaf dimensions, panicle fertility and grain weight. Based on the discriminating characters proposed here for further exploitation, intraspecific lines were grouped into five clusters, two of which (G4 and G5) contained the best lines for vegetative (G4) and productive (G5) characters.